One Decade of Unnatural Deaths in Yazd Province: 2003-2013 - mohamad hassan lotfi; mohammad javad amirian; ali dehghani; hossein falahzadeh; omid emami (Shahid Sadoughi University of Medical Sciences, 2016)
Abstract Introduction: Death is defined as the permanent loss of all signs of life at any time after birth (Irrevocable disappearance of all vital signs after birth). Unnatural deaths seem to be either suspicious or  unexpected. Deaths that occur suddenly and their causes need to be investigated, are termed unnatural deaths. According to the death certificate contents of Ministry of Health and Forensics, if the cause of death is unnatural, the corpse will be submitted to the forensic medicine departments in 19 cases in order to determine the death cause and to issue the burial permit.   Material & Methods: In this descriptive study, the data were extracted from unnatural death cases in the province of Yazd during 2003 to 2013 recorded by Yazd Forensic Medicine. Results: During 2003 -2013, 5552 cases of unnatural deaths were recorded by the Forensic Medicine of Yazd, out of which 4373 cases of unnatural deaths were caused by road traffic accidents (outside and inside the city), 89 deaths from electrocution, 439 deaths from poisoning, 72 deaths from drowning, 129 deaths from asphyxia (by carbon monoxide), 56 deaths from work incidents, and 394 deaths from burns. The group of males aged 20-29 years allocated the highest number of unnatural deaths to themselves. Conclusion: Road traffic accidents are the second leading cause of unnatural deaths in Iran. The number of unnatural death incidents in men is more than women indicating that men are more exposed to risk factors than women, though regarding the deaths due to the burns, women are exposed to the high risk factors.